Kikuchi-Fujimoto Disease Preceding Overlap Syndrome of Sjögren’s Syndrome and Systemic Lupus Erythematosus: Literature Review Based on a Case Report - Cindy Cindy; Suryo Anggoro Kusumo Wibowo; Anna Ariane; Rudy Hidayat (Acta Medica Indonesiana, 2024)
Kikuchi-Fujimoto disease (KFD) is a benign, self-limiting histiocytic necrotizing lymphadenitis systemic disorder with unknown etiology. KFD has been known for half a century, but difficulties in distinguishing it remain. Its diagnostic significance is related to the increasing prevalence of KFD with autoimmune diseases in various timeframes. Systemic lupus erythematosus (SLE) is the most prevalent autoimmune connective tissue disease (AICTD) appearing alongside KFD. An 18-year-old female presented with acute muscle weakness, shortness of breath, fever, and significant weight loss for 5 months before admission. Pain and morning joint stiffness had been felt for 9 months. One year ago, she lumped her right neck and was diagnosed with KFD from the excision biopsy and immunohistochemical staining (CD68). Creatine-kinase enzymes and C-Reactive protein were elevated with a high anti-Ku and anti-Jo-1 negative level. There was a low level of complements, high anti-nuclear antibody titer, with positive anti-SS-A. Sialometry and Schirmer test showed reduced salivary and lacrimal gland production. We diagnosed this patient as having an overlap syndrome preceded by KFD. The AICTD involved was Sjögren’s syndrome and SLE. Although KFD is considered a self-limiting disease, its occurrence should be noticed regarding the possibility of other autoimmune conditions. KFD usually coincides with AICTD, although it could also precede or occur afterward. This case is reported to raise awareness of the overlap syndrome preceded by KFD.